Multi‐state reliability assessment for shipboard hybrid turbine‐diesel generation system with redundancy and aging effects - Xu, Yifan; Shi, Yuedong; Xiong, Zihao; Yang, Haojie (Quality and reliability engineering international, 2023)
Complex system structures, dynamic energy demands, and tough operating environment pose a huge challenge to reliability assessment and risk control. Taking multi‐state, redundant structure and aging impact into account, reliability assessment for shipboard hybrid turbine‐diesel generation system is studied. This work adopts a comprehensive method combining the Markov method and universal generating function (UGF): the Markov method is used for reliability modeling at the unit level, and then synthesized and calculated through UGFs to obtain system‐level reliability. Based on the above methodology, this work presents a multi‐state system (MSS) model with different configuration structures and failure rate types, then compares the availability evaluation results of the single power generation system, the hybrid power system with redundancy and aging effects. The results show that (1) redundant design effectively improves system availability to meet power supply requirements; (2) in the case of system aging and imperfect repair, redundant configuration and power distribution can significantly improve the availability of power supply to be almost unaffected by aging, and effectively reduce the risk of performance failure; and (3) when the redundancy is applied, the system power supply availability is not sensitive in the high‐value range of the redundant installed capacity ratio, but sensitive in the high‐value range of effective coefficient about power compensation control.